lncRNA CERS6‐AS1 as ceRNA promote cell proliferation of breast cancer by sponging miR‐125a‐5p to upregulate BAP1 expression - Yan, Liang; Li, Kai; Feng, Zunyong; Zhang, Yizongheng; Han, Renrui; Ma, Jinzhu; Zhang, Jieling; Wu, Xu; Liu, Haijun; Jiang, Yuxin; Zhang, Yao; Zhu, Yiping (Molecular carcinogenesis, 2020)
Long noncoding RNAs (lncRNAs) can act as oncogene and tumor suppressor genes in many types of cancers including breast cancer (BC). Our previous study has indicated microRNA (miR)‐125a‐5p was downregulated and function as a tumor suppressor in BC. However, its upstream regulation mechanism is still unclear. In this study, we used bioinformatics algorithms, RNA pulldown assay, and dual‐luciferase reports assay to predict and confirm lncRNA CERS6‐AS1 interacted with miR‐125a‐5p. Then we found CERS6‐AS1 was upregulated in BC tissues. Experimental results of tumor growth in nude mice show that CERS6‐AS1 promotes tumor growth. Furthermore, CERS6‐AS1 regulated BC susceptibility gene 1‐associated protein 1 (BAP1) expression via sponging miR‐125a‐5p via Western blot analysis and quantitative polymerase chain reaction arrays. Finally, we showed that miR‐125a‐5p had opposing effects to those of CERS6‐AS1 on BC cells, demonstrating that CERS6‐AS1 may promote cell proliferation and inhibit cell apoptosis via sponging miR‐125a‐5p. Our results indicated CERS6‐AS1 promote BC cell proliferation and inhibit cell apoptosis via sponging miR‐125a‐5p to upregulate BAP1 expression.